SPECIFICITY OF TRAINING FOR PROFESSIONAL DEVELOPMENT OF TEACHERS IN ECONOMIC SPECIALTIES BASED ON FOREIGN EXPERIENCE - Klinkov, G.T (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
Vocational training of teachers in individual countries should not be considered as a measure that has an immediate impact on the learning process. The teaching profession has over the years adopted a certain, conservative model of development and improvement. The experience in the specific subject area has turned into an immediate professional experience and subsequently also in the routine. The development of qualification standards and standards puts first the requirement to define the subject of such multilevel activity. The professional level and the status of the teacher most fully reveal the specificity of such a subject. Differences in qualifications, methodology, and model across countries lead to the emergence of an understanding of an object. Differences in qualifications, methodology, and model across countries lead to the emergence of an understanding of an object. In the empirical analysis related to the development of the thesis, the differentiating components are mainly related to revealing the institutional nature of such preparation in most of the presentations. In the countries of Europe, and especially in those who once built the Eastern Bloc, the qualification activity is measured in the degrees and courses that the respective teachers have completed after they have acquired a teaching qualification. In the United States and the UK, the teacher's qualification activity is primarily related to the protection of his / her professional status at any time in the aptitude test. Teachers develop exclusively on the basis of the qualification within the subject area taught. The training is extremely dynamic, with many open lessons, discussions, discussion of educational innovations within the educational institution.